WORKSHOP PENYUSUNAN PENELITIAN TINDAKAN KELAS (PTK) BAGI GURU SMK KABUPATEN TANAH DATAR - Donny Fernandez; R. Chandra; Hasan Maksum; Wanda Afnison (PAKAR Pendidikan, 2018)
Many can be used to improve the quality of teachers (teachers), among others, the implementation of Classroom Action Research (PTK). Closed education will increase if teachers have and compose a diagogic, personality, competence, and professional competency. PTK is the most appropriate step to improve the quality of learning. This quality improvement will positively affect teachers and teachers. For teachers, PTK is a reflective action over the learning that it does. Selamaini, the teacher is still considered and assumes his or her other resources out of less effort to improve the model and the learning model used. By performing the TOD, the teacher will know the actual condition that he or she faces. The workshop participants were provided with knowledge about the aspects of PTK sertacar in the preparation of a good PTK and hope that they could provide refreshment to teachers relating to the TOD, so that the teachers could do the research as well as to solve the problem of the teaching process they lead. In addition, the objective is also to stimulate teachers to produce a written article published in the field of education. In the case of the Service to the community this teacher is directly guided so as to be able to make the PTK in a separate, multi-disciplinary / offshore environment. From the activities undertaken by the team found a very significant improvement in terms of understanding of teachers in preparing the PTK. This is obtained from the pre test (question and answer) conducted ahead of the activity and post test post activities. Although there is a significant increase in understanding, there is still a need for teachers' independence and intuition in understanding the compilation of TOD more deeply. The Community Service Team provides wide access for workshop participants to communicate both orally and through social networking so that the competence can be developed. In addition, the team devotion to the community also provides modules and literature that can be used as a reference in the preparation of PTK.